Ret receptor tyrosine kinase sustains proliferation and tissue maturation in intestinal epithelia. (12th September 2017) - Perea, Daniel; Guiu, Jordi; Hudry, Bruno; Konstantinidou, Chrysoula; Milona, Alexandra; Hadjieconomou, Dafni; Carroll, Thomas; Hoyer, Nina; Natarajan, Dipa; Kallijärvi, Jukka; Walker, James A; Soba, Peter; et al.
Abstract: Expression of the Ret receptor tyrosine kinase is a defining feature of enteric neurons. Its importance is underscored by the effects of its mutation in Hirschsprung disease, leading to absence of gut innervation and severe gastrointestinal symptoms. We report a new and physiologically significant site of Ret expression in the intestine: the intestinal epithelium. Experiments in Drosophila indicate that Ret is expressed both by enteric neurons and adult intestinal epithelial progenitors, which require Ret to sustain their proliferation. Mechanistically, Ret is engaged in a positive feedback loop with Wnt/Wingless signalling, modulated by Src and Fak kinases. We find that Ret is also expressed by the developing intestinal epithelium of mice, where its expression is maintained into the adult stage in a subset of enteroendocrine/enterochromaffin cells. Mouse organoid experiments point to an intrinsic role for Ret in promoting epithelial maturation and regulating Wnt signalling. Our findings reveal evolutionary conservation of the positive Ret/Wnt signalling feedback in both developmental and homeostatic contexts. They also suggest an epithelial contribution to Ret loss‐of‐function disorders such as Hirschsprung disease. Synopsis: Ret secures the proliferative capacity of adult fly intestinal stem cells (ISC) and mouse postnatal gut development. The intestinal epithelium of both Drosophila and mouse expresses the Ret receptor tyrosine kinase. Ret is autonomously required for ISC proliferation at homeostasis and under stress, and contributes to age‐related intestinal dysplasia. Ret induces Src kinase activation, and maintains Wg/Wnt‐signaling in gut progenitors. Organoids of Ret‐deficient mice exhibit branching defects and incomplete transition from foetal to adult tissue. Abstract : Ret maintains fly intestinal stem cells and mouse postnatal gut development.